EXERCISE AND GESTATIONAL DIABETES - Suwanpakdee, Walailak; Buddum, Maliwan; Dulyakasem, Uthoomporn (Journal of MCU Nakhondhat, 2020)
Diabetes is a common complication in pregnant women. It is caused by changes in the body and disorders of carbohydrate metabolism. As a result, pregnant women have high levels of sugar in the bloodstream and lead to complications for pregnant women and the fetus, such as miscarriage, dystocia, Postpartum hemorrhage, Pregnancy Induce Hypertension, Intra Uterine Fetal Death, Macrosomia and congenital disability. Pregnant women can prevent or reduce the risk of these complications by controlling the level of sugar in the bloodstream with dietary control and exercise methods. Most pregnant women exercise less because they believe that exercising can harm the fetus, which can lead to miscarriage and the lack of knowledge to exercise during pregnancy properly. Exercise in combination with dietary control can better control sugar levels in the bloodstream rather than control with diet only. The right exercise method for pregnant women should exert only the upper muscles of the body and minimal impact on the abdominal muscles, such as walking, swimming and yoga, etcetera. The right exercise for women with gestational diabetes is walking. A good workout should be done 3 times a week or more. It takes approximately 30 minutes for a walk, moderate strength, which results in the body being able to use glucose as more energy. This enhances insulin efficacy, reduces the level of sugar in the bloodstream, and reduces the likelihood of complications during pregnancy.